(untitled) (Politeja, 2019)
Russian geopolitical thought after the collapse of the USSR can be classified in different ways. However, it always remains under the influence of the same conditions (the trauma of a historical downfall) and proposes clear indications for the foreign policy of the state. The article presents a preliminary view of some directions in Russian geopolitical thought from the point of view of their origin. The study focuses on seven trends: the visions of Great Russia in a multipolar world order, Neo-Eurasianism, the insular theory, military geopolitics, the thought of political geographers, the geopolitics of the Russian World doctrine with its varieties in the form of information geopolitics and cyber- geopolitics, and, last but not least, geoeconomics. A typological study of contemporary Russian geopolitical thought reveals two developmental tendencies: one aiming at radical and ideological concepts and the other proposing a semi-scientific approach.